Community ambulation in people with lower limb amputation: An observational cohort study. Issue 3 (22nd January 2021) - Damiani, Carlo; Pournajaf, Sanaz; Goffredo, Michela; Proietti, Stefania; Denza, Gabriele; Rosa, Benedetta; Franceschini, Marco; Casale, Roberto
Abstract : Abstract: Lower limb amputation (LLA) is still a health issue requiring rehabilitation and long-term care even in industrial societies. Several studies on subjects with LLA have been focused on the efficacy of rehabilitation and factors influencing the use of prosthesis. However, literature data on the recovery of ability to walk outdoors, and thus to participate in social life in this population is limited. To investigate potential correlations between socio-demographic and clinical factors, and the use of the prosthesis for indoor and/or outdoor walking referred to as community ambulation (CA) in subjects with LLA. An observational cohort study on 687 LLA subjects was conducted. Socio-demographic and clinical characteristics of 302 subjects who received similar rehabilitative treatment with respect to the standard protocol were collected by a telephone survey with a structured questionnaire. The CA recovery, in terms of patient's autonomy and participation, assessed by Walking Handicap Scale, was considered as the main outcome. The univariate analysis demonstrated statistical significant positive correlation between CA and gender (χ 2 = 3.901, P = .048); amputation level (χ 2 = 24.657, P < .001); pre-LLA (χ 2 = 6.338, P = .012) and current work activity (χ 2 = 25.192, P < .001); prosthesis use (χ 2 = 187.037, P < .01); and time from LLA (r = 0.183, P < .001); increasing age was negatively correlated with the outcome (r = –0.329, P < .001), while pain intensity was not significant. Being male (75.4%); trans-tibial (TT) amputation level (9.79%); working before (3.81%) and after LLA (7.68%); and the prosthesis use (24.63%) increased the probability of CA recovery. Multivariate binary logistic regression analysis confirmed that the prosthesis use ( P < .001) and TT amputation level ( P = .042) are predictors of a positive outcome (Walking Handicap Scale 4–6). These findings highlight the importance of the use of prosthesis in people with LLA for the restoration of a good capacity of participation (CA), especially in subjects with TT amputation level. The identification of predictive factors may help tailor-made rehabilitation approaches addressing an earlier reintegration to social life. Abstract : Supplemental Digital Content is available in the text